Factors influencing female labor force participation in Egypt and Germany: A comparative study - Sara Hassan Hosney (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper aims to identify the major factors influencing female labor force participation (FLFP) in Egypt and Germany. On a narrow scope and given the unclear relationship between educational attainment and Egyptian FLFP, this paper seeksto examine the effect of educational attainment on the Egyptian FLFP while considering other personal and household factors. On a broader scope, the literature on FLFP illustrates that certain personal and household characteristics determineFLFP. However, the question remains, to what extent these determinants differ between Egypt and Germany. This paper attempts to shed light on understanding if and how specific demographic factors affect the Egyptian FLFP in comparison with the German FLFP. Limited dependent variable technique; Probit model is utilized to determine which factors influence FLFP in both countries. The cross sectional analysis is conducted through the use of the 2012 Egyptian Labor Market Panel Survey (ELMPS) in collaboration with Egypt's Central Agency for Public Mobilization and Statistics (CAPMAS) and the 2012 German Socio-Economic Panel (SOEP). Findings indicate that indeed higher educational attainmentincreases the Egyptian female's predicted probability of participating in the labor market. Additionally, the comparative study showed that number of factors affect FLFP in both countries, some of which has a positive influence as years of schooling and age while others with a negative impact as being a married women, living in urban areas and number of children. On the other hand some other variables impact each country differently as wealth. Additionally, it was evident that years of schooling has a higher marginal impact on Egyptian FLFP yet, age, being married and number of children have a higher marginal effect on German FLFP.
Keywords: 330